Diagnosis and Correction of Impaired Lipid Peroxidation in Terminal States: Experimental Study - A. S. Razumov; A. Ya. Yevtushenko (Общая реаниматология)
Ischemic and early postresuscitative lipid peroxidation (LPO) changes in the cortex and subcortical structures of the brain, the left and Spiegelian lobes of the liver, the cortex and medulla of the kidney, and plasma were studied in experiments on cats, by using a model of 5-minute clinical death from long-term blood loss. At death and in the early postresuscitative period, the LPO changes were ascertained to have qualitative, quantitative, and temporary differences not only in various organs, but also in various structures of the same organ. Excessive reperfusion was shown to play a leading role in postresuscitative LPO activation in the brain. At the same time, the high rate of LPO was not always followed by adequate tissue and plasma accumulation of LPO products and it was revealed only in rather long incubation of homogenates. Not only hyperreperfusion activation of lipid peroxidation, but also its excessive inhibition caused by antioxidantive agents was established to adversely affect resuscitation after a prior terminal condition.